Strategi Konsep Arsitektur Eko-kultur pada Rancangan Rumah Layak Huni di Lahan Rawa/ Gambut Kalimantan Selatan - Dedi Iskandar; Wahyu Prabowo; Ratna Destianti Kusumaningrum (Arsir: Jurnal Arsitektur, 2025)
The problem of Low Income Community, that we called Masyarakat Berpenghasilan Rendah (MBR) to get a house is becoming more complex with limited income, land fulfillment, and design that pays attention to sustainability aspects. Therefore, the purpose of this study is to obtain a house design that is livable, sustainable and affordable according to the needs of MBR that pays attention to local culture and wisdom. By using the design thinking method, this study involves a collaborative and empathetic process to understand the needs of MBR in depth, formularize problems, to produce prototype-based design solutions. This study raises the theme of ecocultural architecture that integrates the principles of ecological sustainability and local wisdom of local culture as an approach in designing a liveable house. From this study, a house design for MBR is produced that is livable, affordable, and pays attention to local culture and wisdom.